2005
DOI: 10.1007/s00114-005-0630-4
|View full text |Cite
|
Sign up to set email alerts
|

Disease and colony foundation in the dampwood termite Zootermopsis angusticollis: The survival advantage of nestmate pairs

Abstract: To determine the impact of inbreeding and outbreeding on disease resistance and survival during colony foundation, nestmate (NM) and non-nestmate (NON) primary reproductives of the dampwood termite Zootermopsis angusticollis were exposed to a single or double dose of conidia of the entomopathogenic fungus Metarhizium anisopliae. Male and female primary reproductive pairs originating from the same parent colony had higher survivorship than NON pairs in control and conidia-exposure treatments. The survival advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
2
24
1
Order By: Relevance
“…Similar to previous studies [22,24,35], nest-mates in our study survived better than non-nest-mates, however, this is probably an artificial situation with little biological relevance as alates participating in natural mass dispersal are unlikely to pair with nest-mates [36 -38]. In N. corniger, workers and soldiers actively exclude or kill alates remaining in a queen-and king-right parent colony after the normal dispersal flights have occurred ( [39], and T. R. Hartke 2007-2009, personal observations), and thus remaining in the natal nest as supplementary or replacement reproductives is unlikely.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [22,24,35], nest-mates in our study survived better than non-nest-mates, however, this is probably an artificial situation with little biological relevance as alates participating in natural mass dispersal are unlikely to pair with nest-mates [36 -38]. In N. corniger, workers and soldiers actively exclude or kill alates remaining in a queen-and king-right parent colony after the normal dispersal flights have occurred ( [39], and T. R. Hartke 2007-2009, personal observations), and thus remaining in the natal nest as supplementary or replacement reproductives is unlikely.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Rosengaus and Traniello (1993) found that laboratory established incipient colonies of Z. angusticollis comprised of nestmate primary reproductives were more likely to survive than those headed by unrelated reproductives, possibly through exposure to novel pathogens harbored by unrelated individuals. Similar results have been reported by Calleri et al (2005) and Fei and Henderson (2003). If sibling headed colonies are also favored in the field, then such outbreeding depression could lead to a disproportionate number of established colonies headed by siblings than would be suggested by analysis of tandem pairs formed after mating flights.…”
Section: Population Differentiationsupporting
confidence: 73%
“…For example, Z. nevadensis alates appear to outbreed (Shellman-Reeve 2001) but secondary reproductives are common in Zootermopsis colonies that have lost one or both primaries (Castle 1934;Light & Illg 1945), probably reducing allelic variation in their offspring (Husseneder et al 1999;Thorne et al 1999;Vargo 2003;DeHeer & Vargo 2004). In addition, nesting ecology (Hamilton 1972), predation on alates (Lepage 1991;Matsuura & Nishida 2002) and disease risk (Rosengaus & Traniello 1993;Rosengaus et al 2000;Calleri et al 2005) may limit dispersal, which could also increase inbreeding (Roisin 1999). Cycles of inbreeding and outbreeding may have influenced the way in which termite colonies adapted to disease, outbreeding generating variation in disease resistance traits and inbreeding maintaining adapted disease-resistant genotypes selected for during colony growth (Thorne & Traniello 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Termites from the 11 inbred and 13 outbred colonies were individually exposed to a conidia-free 0.1% Tween 80 solution, an 8.1!10 3 (low dose) or 4.5!10 5 (high dose) conidia ml K1 suspension of M. anisopliae according to established protocol (Traniello et al 2002;Calleri et al 2005). Because we could not anticipate the number of individuals and their age distribution in each log nest we opened, sample sizes were lower for the high-dose conidia exposure experiments, which were carried out later in the study.…”
Section: Methodsmentioning
confidence: 99%